Gaucher’s Disease – What Should You Know - Podgórska, Dominika; Jurasz, Karolina; Sanecki, Miłosz; Tomczyk, Karolina; Chojnacka, Natalia; Rzeska, Ewa; Klarycki, Jakub; Cymer, Radosław (Quality in Sport, 2024)
Gaucher’s Disease (GD) has a special place among ultra-rare diseases, which is a disease that occurs in less than onein 50 000 persons. The disease is caused by a hereditary autosomal deficiency of the lysosomal enzyme glucocerebrosidase. The pathognomonic feature of GD is the presence of storage cells or gaucher cells in spleen, liver and other organs and tissues. There are several clinical types of gaucher disease, differing in manifestation, prognosis and treatment. It is very important to diagnose the disease early so that the correct treatment can be implemented. Nowadays, it is not uncommon for general practitioners and specialists to make the wrong diagnosis due to the low probability and lack of knowledge of the disease, leading to a worsening patient's condition. A proper examination consists of a medical history, physical examination and targeted radiological examinations, which are of particular importance in the diagnosis due to changes in the body that are not otherwise detectable, but which already offer a chance to make a diagnosis. The latest treatment is based on enzyme replacement therapy, but unfortunately the prognosis in some cases is still unfavourable. This is why early diagnosis and research to find an effective treatment are so important.